Multifidus Muscle Size and Symmetry in Ballroom Dancers with and without Low Back Pain - Smyers Evanson, Alyssa; Myrer, Joseph William; Eggett, Dennis L.; Mitchell, Ulrike H.; Johnson, A. Wayne (International Journal of Sports Medicine, 2018)
The incidence of low back pain (LBP) among elite ballroom dancers is high and understanding associations between muscle morphology and pain may provide insight into treatment or training options. Research has linked multifidus muscle atrophy to LBP in the general and some athletic populations; however, this has not been examined in ballroom dancers. We compared the lumbar multifidus cross-sectional area (CSA) at rest in 57 elite level ballroom dancers (age 23±2.4 years; height, 174±11 cm; mass, 64±10 kg) divided into one of three pain groups, according to their self-reported symptoms, 1) LBP group (n=19), 2) minimal LBP (n=17), and 3) no LBP (n=21). There were no significant difference in demographics between the groups (P>0.05). The LBP group demonstrated significant differences in reported pain and Oswestry Disability Index scores compared to the other two groups. There was no significant difference between groups in multifidus cross-sectional area (P=0.49). Asymmetry was found in all groups with the overall left side being significantly larger than the right (P<0.002). Pain associated with segmental decrease in multifidus CSA was not observed in ballroom dancers with LBP, suggesting other reasons for persistent LBP in ballroom dancers.
Keywords: spine musculoskeletal ultrasound imaging; core strength in dancers; imaging dancers